Vitamin K-Dependent Proteins as Predictors of Valvular Calcifications and Mortality in Hemodialysis Patients - Marcel Palamar; Iulia Dana Grosu; Adalbert Schiller; Ligia Petrica; Madalina Bodea; Alexandru Sircuta; Elisabeta Gruescu; Oana Daniela Matei; Maria Daniela Tanasescu; Ionut Golet; Flaviu Bob (Biomedicines)
Background/Objectives: Vitamin K deficiency in chronic kidney disease (CKD) could potentially occur due to multiple factors, leading to an increased risk of vascular and valvular calcifications. Vitamin K status can be indirectly assessed by measuring the blood levels of vitamin K-dependent proteins (VKDPs), such as matrix GLA protein (MGP). This study aims to examine the relationship between the levels of inactive MGP (dp-uc MGP) and the presence of valvular calcifications, as well as its association with mortality in hemodialysis patients. Methods: We conducted a single-center study that included 45 CKD G5D patients (hemodialysis for 6 months to 10 years) followed up for 24 months. All patients have been assessed at baseline regarding cardiovascular disease (medical history, echocardiography). Moreover, using standard methods, we determined blood biochemistry, complete blood count, and matrix GLA protein. At 24 months of follow-up, we assessed all-cause mortality and cardiovascular mortality. Results: In the studied hemodialysis patients, mean dp-uc MGP was 3285.93 +/− 2092.85 pmol/L. Patients with valvular calcifications had higher levels of dp-uc MGP compared to those without (4521.08 +/− 2263.82 vs. 2487.53 +/− 1446.94 pmol/L, however not statistically significant). The presence and severity of valvular calcifications were significantly associated with the history of treatment with vitamin K antagonists (p < 0.05). After 24 months of follow-up, we found an all-cause mortality rate of 24.4%. The level of dp-uc MGP was higher in the group of patients that died (3884.81 +/− 2439.20 vs. 3133.09 +/− 1925.26 pmol/L, p > 0.05). Patients with more than one valvular calcification on echocardiography had a significantly higher all-cause mortality risk (p = 0.04). In terms of traditional risk factors, we observed an increased risk of all-cause mortality in patients with a history of diabetes mellitus (p = 0.02) and aortic stenosis (p = 0.01). However, other cardiovascular markers, such as coronary heart disease and ejection fraction < 50%, did not have a statistically significant impact on mortality in our patients. Conclusions: In our study, we found that vitamin K deficiency, measured indirectly using the level of VKDP, especially dp-uc MGP, is a predictor of valvular calcifications. Severe valvular calcifications, aortic stenosis, and the presence of diabetes mellitus are risk factors for all-cause mortality in hemodialysis patients.